A fluorescein-based chemosensor for "turn-on" detection of Hg2+ and the resultant complex as a fluorescent sensor for S2− in semi-aqueous medium with cell-imaging application: experimental and computational studies. (11th March 2019) - Mohammad, Hasan; Islam, Abu Saleh Musha; Prodhan, Chandraday; Ali, Mahammad
Abstract : A fluorescein hydrazone based probe selectively recognizes Hg 2+ ion with live cell imaging application. Abstract : A fluorescein hydrazone based conjugate (H2 L 3 ) was synthesized by coupling fluorescein hydrazide (L 1 ) with 2-(pyridin-2-ylmethoxy)-naphthalene-1-carbaldehyde (L 2 ).H2 L 3 was well characterized by several spectroscopic methods such as IR, 1 H, 13 C-NMR and ESI-MS. The probeH2 L 3 exhibited high selectivity and high sensitivity towards toxic Hg 2+ ions in semi-aqueous medium (pH 7.2, 10 mM HEPES) over other metal ions. The significant enhancement in fluorescence emission centered at 520 nm was attributed to the Hg 2+ -induced ring opening of the spirolactam moiety in the fluorescein structure. The 1 : 1 binding ofH2 L 3 to Hg 2+ was established by Job's method and confirmed by ESI-MS + ( m / z ) studies and the binding constant was calculated as (0.43 ± 0.04) × 10 4 M −1 with a detection limit of 1.24 μM. Then again, the[Hg(HL 3 )] + ensemble could be utilized as a reversible fluorescent sensor for S 2− . On addition of S 2− to the[Hg(HL 3 )] + complex, the fluorescence intensity was totally quenched because Hg 2+ in the complex was grabbed by S 2− because of the stronger binding force between Hg 2+ and S 2− . The tentative coordination environment in the[Hg(HL 3 )] + complex was established by DFT studies. The fluorescence "OFF–ON–OFF" mode ofH2 L 3 was examined in the presence of Hg 2+ and S 2− and finds applications in devices with logic gate functions.H2 L 3 also exhibits bio-compatibility and negligible cytotoxicity and is suitable for fluorescence cell imaging of Hg 2+ ions in live HepG2 cells.